DIGITAL ZAKAT IN THE ERA OF ISLAMIC SOCIAL FINANCE: A SYSTEMATIC REVIEW OF ECONOMIC IMPACT AND INSTITUTIONAL TRANSFORMATION - Axel Puri Hatomono (PT. Samudra Solusi Profesional, 2024)
The rapid advancement of digital technology has significantly transformed the landscape of Islamic social finance, particularly in the management of zakat. Digital zakat platforms such as mobile applications, online payment systems, QR-based transactions, and Islamic fintech services have emerged as innovative mechanisms to enhance the efficiency, transparency, and accessibility of zakat collection and distribution. Despite the growing adoption of digital zakat systems, there remains a limited consolidated understanding of their broader economic implications, especially concerning poverty alleviation, financial inclusion, and socio-economic development. This study aims to systematically review existing scholarly literature on zakat digitalization and its economic impact. Employing a systematic literature review (SLR) approach, this study synthesizes peer-reviewed articles published between 2015 and 2025 sourced from reputable academic databases. The review process follows the PRISMA framework to ensure methodological rigor in article identification, screening, and analysis. The selected studies are examined to identify dominant themes, technological drivers, implementation challenges, and the economic outcomes associated with digital zakat systems. The findings indicate that zakat digitalization contributes positively to operational efficiency by reducing administrative costs, accelerating transaction processes, and improving financial transparency. Digital platforms also enhance donor trust and participation, particularly among younger and technologically literate populations. Furthermore, evidence suggests that digital zakat supports financial inclusion and strengthens the socio-economic empowerment of beneficiaries by facilitating targeted and timely distribution. However, persistent challenges, such as digital literacy gaps, regulatory constraints, cybersecurity risks, and concerns regarding sharia compliance, continue to hinder the full realization of its potential. This review concludes that zakat digitalization represents a strategic opportunity to optimize the economic role of zakat within Islamic economies. Nevertheless, its success depends on integrated policy support, institutional readiness, and continuous innovation. The study provides theoretical contributions to Islamic finance literature and offers practical insights for policymakers, zakat institutions, and fintech developers.